Kontekstualisasi Hadis Tentang Hijrah Dalam Akun Instagram Hijrahfest: (Pendekatan Hermeneutika Ktirtis Habermas) - Muhammad, Afda Nahied (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
The fashion trend has become unstoppable, as evidenced by fashion now being endless consumption. The hijrah trend has become an interesting fact in the millennial era. Hijrah is not merely interpreted literally; nowadays, the hijrah trend has penetrated the world of fashion, attracting the attention of many people. This article discusses the expansion of the meaning of hijrah in social media, resulting in multiple interpretations of hijrah itself. Habermas’s hermeneutics, with its dialogical and emancipatory approach, is presented as a solution for communicating these meanings, which are then used to understand social behavior directed by the prevailing meanings. This article employs a literature research method with a descriptive-analytical approach. It concludes that hijrah is not a pretext for organizing various events to attract many enthusiasts using the slogan ’hijrah’ as a promotional tool to market clothing products claiming to be ’syar’i’ with the aim of gaining worldly value within the economic business framework.